Cytology technique: development of a simple spot method for cultured cell suspension (Faculty of Medicine Universitas Indonesia, 2010)
Aim To develop a simple spot method to attach cultured cells in suspension on to a glass slide. Methods We compared three approaches using both conventional and special glass slide (Shandon-Polysin), either without additional fetal bovine serum (FBS), or with addition of 3 or 10 μl of FBS to a 20 μl sample (altogether there were six approaches). The slides were examined qualitatively for the background color, boundary color and intactness, and whether there were folded and detached parts. Further, for each slide, the attached intact cells were counted, and the percentage of attached intact cells per number of spotted cells was calculated. The difference in attach intact cells between different approaches was analyzed by ANOVA using SPSS 13.0 for windows. Results There were no significant difference in the percentage of attached intact cells between the six approaches (P= 0.804), though the approach using special glass slide without additional FBS (FBS final concentration 5%) yield the highest percentage of attached intact cells, showed clean background without folded parts. Conclusions We have developed a simple spot method for cultured cell suspension, and the best approach to make spot specimen is using special glass slide with 5% FBS in the cell suspension. (Med J Indones 2010; 19:26-31) Keywords: spot specimen, special glass slide, fetal bovine serum